Understanding corporate governance of healthcare quality: a comparative case study of eight Australian public hospitals - Alison Brown (BMC, 2019)
Abstract Background Patients are sometimes harmed in the course of receiving hospital care. Existing research has highlighted a positive association between board engagement in healthcare quality activities and healthcare outcomes. However, most research has been undertaken through surveys examining board engagement in a limited number of governance processes. This paper presents evidence of a comprehensive range of processes related to governing healthcare quality undertaken at the corporate governance level. This provides a more detailed picture than previously described of how corporate governance of healthcare quality is enacted by boards and management. Methods A comparative case study of eight Australian public hospitals was undertaken. Case studies varying is size and location were selected from two Australian states. Data collection included a review of key governance documentation, semi structured interviews with board members and senior management and an observation of a board quality committee meeting. Thematic analysis was undertaken to identify processes related to key tasks in governing healthcare quality. Results Two key tasks in the corporate governance of healthcare quality, evaluating healthcare quality and overseeing quality priorities, were examined. Numerous processes related to these two tasks were found. Case studies, while found to be similar in engagement on previously identified processes, were found to differ in engagement in these additional processes. While generally low levels of engagement in processes of overseeing quality priorities were found, cases differed markedly in their engagement in evaluating healthcare quality processes. Additional processes undertaken at some case studies represent innovative and mature responses to the need for effective corporate governance of healthcare quality. In addition, a group of processes, related to broader governance taskwork, were found to be important in enabling effective corporate governance of healthcare quality. Conclusion The work of governing healthcare quality, undertaken at the corporate governance level, is redefined in terms of these more detailed processes. This paper highlights that it is how well these key tasks are undertaken that is important in effective governance. When processes related to key tasks are omitted, the rituals of governance may appear to be satisfied but the responsibility may not be met. Boards and managers need to differentiate between common approaches to governance and practices that enable the fulfilment of governance responsibilities. This study provides practical guidance in outlining processes for effective corporate governance of healthcare quality and highlights areas for further examination.